Cutaneous Anthrax Outbreak in Rajshahi District - Haque, Md Azizul; Khan, Mohammad Mahbubur Rahman; Sharmin, Laila Shamima; Alam, Khandaker Md Faisal; Rahman, Md Khalilur; Alam, Md Shah (TAJ: Journal of Teachers Association, 2018)
Anthrax is an acute, zoonotic infectious disease caused by gram positive, aerobic, spore forming bacterium Bacillus anthracis. Cutaneous anthrax is the commonest form of anthrax, comprising more than 95% of cases. Incidence of anthrax is declining in the developed countries; but because of inadequate livestock vaccination program, it remains a public health hazard in the developing countries. Several cutaneous anthrax outbreaks were observed in Bangladesh over the last few years and the latest one occurred in Lalitnagar village, Godagari Upazilla of Rajshahi district in September 2016. We are reporting clinico-demographic profile and treatment outcome of the affected patients with the aim of increasing awareness among the clinicians and public health experts. TAJ 2017; 30(1): 17-20